Iterative Signal Detection for Diffusion-Based Molecular Communications - Thakur M.S.; Sharma S.; Bhatia V. (My University, 2025)
Inter-symbol interference (ISI) due to slow-moving molecules is one of the key limitations affecting throughput of a diffusion based molecular communication (MC). In this paper, we propose novel ISI mitigation approaches for diffusion based MC systems. The first approach uses weighted sum (WS) to enhance the received signal-to-ISI plus noise ratio (SINR) by exploiting the apriori characteristics of the diffusion channel impulse response. In the second approach, an iterative method estimates the ISI in a frame using the block-wise data symbol detection and subtracts this estimated ISI before the signal detection. Both the proposed methods improve the MC system's performance as compared to the conventional signal detection method. Further, we have analyzed the combined WS and iterative method, resulting in further improvement in the performance. Furthermore, the effect of various system parameters such as frame duration, diffusion coefficient, and the distance between transmitter and receiver is analyzed. © 2015 IEEE.